2002
DOI: 10.1038/sj.bjc.6600257
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, tumour necrosis factor α and interleukin-1β in patients with renal cell carcinoma

Abstract: As regulators of malignant cell behaviour and communication with stroma, cytokines have proved useful in understanding cancer biology and developing novel therapies. In renal cell carcinoma, patients with inflammatory reactions are known to have poor prognosis. In order to elucidate the relation between renal cell carcinoma and the host, serum levels of inflammatory cytokines, interleukin-6, tumour necrosis factor a, interleukin-1b, were measured. One hundred and twenty-two patients with renal cell carcinoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 18 publications
5
92
1
1
Order By: Relevance
“…In a series of 122 patients with renal cell carcinoma, Yoshida et al (2002) demonstrated that serum levels of TNF-a directly correlated with advanced stage grouping as compared with controls, and suggested that TNF-a could be useful in the early diagnosis of the disease. There has been a single study by Nakashima et al (1998), where TNF-a has been shown to be associated with prostate cancer progression.…”
mentioning
confidence: 99%
“…In a series of 122 patients with renal cell carcinoma, Yoshida et al (2002) demonstrated that serum levels of TNF-a directly correlated with advanced stage grouping as compared with controls, and suggested that TNF-a could be useful in the early diagnosis of the disease. There has been a single study by Nakashima et al (1998), where TNF-a has been shown to be associated with prostate cancer progression.…”
mentioning
confidence: 99%
“…In RCC, inflammatory reactions are correlated with a poor patient prognosis. The serum levels of TNF-a are significantly higher and correlated with tumor size in RCC (7,8). In addition, infliximab, a chimeric anti-human TNFa antibody, was effective in the therapy of RCC patients in 2 phase II studies (8).…”
Section: Introductionmentioning
confidence: 97%
“…In patients with RCC, plasma TNF-a is significantly higher and associated with tumor size, grade, and stage. 22 Therefore, we sought to determine whether Gal-1 was involved in the transcriptional upregulation of CXCR4 induced by TNF-a. As shown in Figure 5, A and B, TNF-a increased protein levels of Gal-1 and CXCR4 and induced CXCR4 promoter activity in shLuc-or shLacZ-infected A-498 control cells.…”
Section: Gal-1 Promoted Cell Motility and Clonogenicity Of Rcc Cells mentioning
confidence: 99%